Does the Decoupling Reform Affect Agricultural Employment in Sweden? Evidence from an Exogenous Change - Martin Nordin (Lund University, School of Economics and Management, Department of Economics, 2013)
This study uses aggregated municipality data, for the years 2001 to 2009, to explore whether direct payments to farmers affect agricultural employment in Swedish municipalities. The decoupling reform in 2005 included a new grassland support payment accompanied by management obligations that had unexpectedly high redistributive consequences as it greatly increased CAP payments to municipalities with large areas of grassland. In some municipalities, total payments more than doubled. Thus, since the reform seems exogenous to the behavior of farmers and the regional economy, the reform can be used to identify a subsidy effect. We find that a permanent increase in agricultural employment can be attributed to the new grassland support. Our results indicate that the grassland support generates an additional job at a cost of SEK 250,000, relative to the average agricultural wage of SEK 333,000. However, the subsidy effect is largely keeping jobs in agriculture, i.e. the grassland support may be slowing down the process of structural change in grassland regions.
Keywords: H50; J18; J21; Q10; 330; agriculture; subsidies; employment effect; single farm payment; Common Agricultural Policy; EU